1982
DOI: 10.1128/aac.21.4.688
|View full text |Cite|
|
Sign up to set email alerts
|

Variables in demonstrating methicillin tolerance in Staphylococcus aureus strains

Abstract: Certain technical considerations which affected the status of methicillin tolerance in Staphylococcus aureus strains were studied. Methods which consistently demonstrated tolerance or intolerance of a given strain were avoidance of inoculum splashing, use of stationary-phase inoculum, 24-h tube incubation, and minimization of antibiotic carry-over. These studies suggested a need for the establishment of a standardized reference for the determination of tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…While the growth phase may not have a significant effect on MIC tests, as demonstrated by Barry et al (7) and Kim and Anthony (56), most investigators (48,56,70,75,108,114) have confirmed the importance of using log-phase growth for the inoculum for MBC tests. When stationary-phase growth is used, the number of surviving or "persisting" organisms tends to increase after 24 h of incubation, and therefore the MBC result may be artificially high.…”
Section: Introduction Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…While the growth phase may not have a significant effect on MIC tests, as demonstrated by Barry et al (7) and Kim and Anthony (56), most investigators (48,56,70,75,108,114) have confirmed the importance of using log-phase growth for the inoculum for MBC tests. When stationary-phase growth is used, the number of surviving or "persisting" organisms tends to increase after 24 h of incubation, and therefore the MBC result may be artificially high.…”
Section: Introduction Introductionmentioning
confidence: 86%
“…As noted earlier, Taylor et al (108) demonstrated that early agitation was helpful only with a large initial inoculum volume of 1.0 ml, and not when <0.1 ml was used. Early agitation may remove viable bacterial cells from continued exposure to the antimicrobial agent (48,108). A sample size of 0.1 ml for the subculture gives sufficient precision to the endpoint determination used in the evaluation of the MBC result.…”
Section: Proposed Mbc Test Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The drug carryover phenomenon has been described for several antibiotics, e.g., ␤-lactams, fluoroquinolones, and clofazimine, and also for antiseptics, such as betadine, chlorhexidine, and niacinamide (2,3,4,7,9). Some methods that can be used to overcome this phenomenon are available, but none of them can be universally applied.…”
Section: Discussionmentioning
confidence: 99%